Effects of a single intravenous bolus of fentanyl on the minimum anesthetic concentration of isoflurane in chickens (Gallus gallus domesticus) - Rocha, Rozana W. da [UNESP]; Escobar, Andre [UNESP]; Pypendop, Bruno H.; Zangirolami Filho, Darcio [UNESP]; Thiesen, Roberto; Gava, Fabio N. (Elsevier B.V., 2017)
Objective To assess the temporal effects of a single fentanyl intravenous (IV) bolus on the minimum anesthetic concentration (MAC) of isoflurane in chickens and to evaluate the effects of this combination on heart rate (HR) and rhythm, systemic arterial pressures (sAP) and ventilation. Study design Prospective experimental trial. Animals Seventeen adult chickens weighing 1.8 +/- 0.2 kg. Methods Individual isoflurane MAC for 17 chickens was previously determined using the bracketing method. Chickens were anesthetized with isoflurane to evaluate the effects of a single IV fentanyl bolus (10 or 30 mu g kg(-1)) on isoflurane MAC over time using the up-and-down method. Ventilation was controlled. The isoflurane MAC reduction was estimated by logistic regression at 5 and 15 minutes after fentanyl administration. In the second phase, seven chickens were anesthetized with isoflurane, and fentanyl was administered (30 mu g kg(-1)) IV over 1 minute during spontaneous ventilation and HR and rhythm, sAP and ventilation variables were measured. Results At 5 minutes after IV administration of fentanyl (10 or 30 mu g kg(-1)), isoflurane MAC was significantly reduced by 17.6% (6.1-29.1%) [logistic regression estimate (95% Wald confidence interval)] and 42.6% (13.3-71.9%), respectively. Isoflurane MAC reduction at 15 minutes after IV administration of fentanyl (10 or 30 mu g kg(-1)) was 6.2% (-0.6 to 12.9%) and 13.2% (-0.9 to 27.3%), respectively; however, this reduction was not significant. No clinically significant cardiopulmonary changes or arrhythmias were detected after the administration of fentanyl (30 mg kg(-1)). Conclusions and clinical relevance Administration of a single fentanyl bolus induced a dosedependent and short-lasting reduction in isoflurane MAC. The higher dose induced no significant cardiopulmonary depression in isoflurane-anesthetized chickens during spontaneous ventilation. In chickens anesthetized with isoflurane, the clinical usefulness of a single fentanyl bolus is limited by its short duration of effect.
Keywords: balanced anesthesia; birds; fentanyl; inhalation anesthesia; opioids; ventilation